A management of juvenile idiopathic arthritis (JIA) associated anterior uveitis with special references to Pittaja Adhimantha, by an Ayurvedic and modern aspect- a single case study.: Array - Telgote, Dipika (Ayurline: International Journal of Research in Indian Medicine, 2022)
Juvenile Idiopathic Arthritis (JIA) and chronic uveitis is defined as arthritis of at least 6 weeks of duration without any identifiable cause in children younger than 16 years. This is the most common cause of uveitis in children.Uveitis strictly means the inflammation of uveal tissue only. But practically, there is always some associated inflammation of adjacent structures such as retina, vitreous, sclera, and cornea. Uveitis is classified on the basis of anatomical, clinical, etiological, and pathological. The International Study Group described anatomical classification. So, it is classified into anterior, intermediate, posterior, and pan uveitis. The anterior uveitis is inflammation of uveal tissue from iris up to the pars plicata of ciliary body. This term include iritis, iridocyclitis. The Standard uveitis working group has described the disease acute, chronic and recurrent on the basis of its course. Main symptoms of acute anterior uveitis are pain, photophobia, redness, lacrimation and decreased vision. In chronic uveitis, the eye may white with minimal symptoms even in the presence of sign of severe inflammation. Our aim is to assist in the diagnosis and short term and long-term treatment of ayurveda and modern can prevent possible serious complications such as Cataracts, Glaucoma, Retinal complication etc. Anterior uveitis is mostly correlated with Pittaja Adhimanth in Ayurveda. The sign and symptoms in anterior uveitis can be compared with Pittaja Adhimantha and its treatment on the basis of Doshas and Samprapti in Ayurveda. this case study of patient with anterior uveitis who showed marked improvement is presented.